114 A PILOT STUDY INVESTIGATING THE ASSOCIATION BETWEEN MINDFUL EATING AND LIVING (MEAL), WEIGHT LOSS, AND BIOLOGIC MARKERS OF INFLAMMATION AND METABOLISM IN OBESE SUBJECTS. Issue 1 (1st January 2007) - Sloan, A. L.; Colleran, K. M.; Shelley, B.
Abstract : Background and Objective: In obese subjects, the effects of mindfulness, a type of meditation and life attitude, on weight loss and biologic markers of inflammation and metabolism have not been previously assessed. Current pharmacologic treatment has not proven to be effective in sustaining weight loss. We thus sought to investigate a method of behavioral change that might demonstrate a permanent solution to both achieving and maintaining weight loss. The goal of this pilot study was to identify potential relationships between a mindfulness-based eating curriculum entitled Mindful Eating and Living (MEAL) and anthropometric and biologic measures. Methods: Ten obese subjects with a body mass index (BMI) of 36.9 ± 6.2 kg/m 2 underwent a 6-week mindfulness training course via a mindfulness curriculum adapted to address eating. Anthropometric and laboratory evaluation at baseline, 6 weeks, and 12 weeks were obtained. Results: Ten subjects completed the 6-week training course. An analysis including all subjects, with the last observation carried forward for one who did not complete the final BMI and laboratory evaluation, demonstrated a decrease in body weight at 6 weeks (mean [± SD], −3.0 ± 1.9 kg; p = .0009) and 12 weeks (mean [± SD], −3.3 ± 1.8 kg; p = .0004) and a decrease in BMI at 6 weeks (−1.1 ± 0.7 kg/m 2 ; p = .0008) and 12 weeks (−1.2 ± 0.6 kg/m 2 ; p = .0003). Also seen was a decrease in hsCRP at 12 weeks (−0.08 ± 0.08 mg/dL; p = .04) and a decrease in PAI-1 at 6 weeks (−19.4 ± 13.3 IU/mL; p = .01). No statistically significant changes were seen in fasting lipids, glucose, insulin, interleukin-6, tumor necrosis factor α, adiponectin, or waist-hip ratio. Conclusions: A brief mindfulness-based training course specifically addressing eating resulted in statistically significant decreases in body weight, hsCRP, and PAI-1. Study limitations include the small number of subjects, the absence of a control group, and a short follow-up period. A controlled study including 40 subjects, more rigorous physiologic and biologic measures, and a longer follow-up period is currently under way.